African American education race, community, inequality and achievement ; a tribute to Edgar G. Epps - Allen, Walter Recharde; Spencer, Margaret Beale; O'Connor, Carla; Dano, Ophella; Epps, Edgar G., 1929- (Advances in education in diverse communities ;, 2002)
This volume considers African-American education in the 21st century through the lens of the Chicago School Tradition, at the University of Chicago. The Chicago School Tradition, among other emphases, stressed the optimistic view that all children who do not have serious physical or emotional impairments can do well in school, if provided access to effective teachers, sufficient resources and adequate opportunities to learn. On the occasion of Professor Edgar G. Epps' retirement from the University of Chicago, as Marshall Field IV Professor of Urban Education, this volume includes contributions from several generations of scholars influenced by his work to celebrate his career and contributions to educational research, policy and practice. More broadly, the volume adopts a holistic approach to examine the persistent challenges of deteriorating urban schools and poor educational outcomes for African American students. The volume seeeks to demonstrate how solutions may flow from educational research, theory, policy and practices conducted in the Chicago School Tradition.